Chemical exposure levels in printing and coating workers with cholangiocarcinoma (third report). Issue 6 (25th December 2015) - Yamada, Kenichi; Kumagai, Shinji; Kubo, Shoji; Endo, Ginji
Abstract : Chemical exposure levels in printing and coating workers with cholangiocarcinoma (third report): Kenichi Yamada, et al . Occupational Health Research and Development Center, Japan Industrial Safety and Health Association Objective: This study aimed to identify the chemicals used by five printing workers and one coating worker who developed cholangiocarcinoma and estimate the workers' levels of chemical exposure. Methods: We obtained information on chemicals from the Ministry of Health, Labour and Welfare, Japan, and estimated working environment concentrations of the chemicals in printing and coating rooms and exposure concentrations during the ink and dirt removal processes. We also calculated shift time‐weighted averages of exposure concentrations. Results: All five printing workers were exposed to both 1, 2‐dichloropropane (1, 2‐DCP) and dichloromethane (DCM). The estimated maximum exposure concentrations for each of the five workers were 190 to 560 ppm for 1, 2‐DCP and 300 to 980 ppm for DCM, and the estimated shift average exposure concentrations were 0 to 230 ppm for 1, 2‐DCP and 20 to 470 ppm for DCM. The coating worker was exposed to 1, 2‐DCP, but not DCM. He did not use ink, and thus was subjected to different conditions than the printing workers. The estimated maximum exposure concentration of 1, 2‐DCP was 150 ppm, and the estimated shift time‐weighted average exposure concentration was 5 to 19 ppm. Conclusions: Our findings support the notion that 1, 2‐DCP contributes to the development of cholangiocarcinoma in humans and the notion that DCM may also be a contributing factor. The finding that the coating worker was exposed to 1, 2‐DCP at a lower exposure concentration is important for determining the occupational exposure limit. Furthermore, the subject did not use ink, which suggests that ink did not contribute to the development of cholangiocarcinoma.